Evaluación de la captura de carbono, durante el 1° año de crecimiento y desarrollo de 4 especies forestales Morupa, Capirona, Bolaina y Caoba en la estación experimental El Porvenir - Angulo Panduro, Neivith (2013)
This research study was conducted at the El Porvenir Experimental Station, INIA Tarapoto, Juan Guerra district, San Martin Province, San Martin Department. lt hadas principal aim: To evaluate the carbon capture during the first growth year and development of four forest species "Marupa", "Bolaina", "Capirona" and "Mahogany" on the El Porvenir Experimental Station- Tarapoto, and as specific aims: a) To sow botanical seed of the species "Marupa", "Bolaina", "Capirona" and "Mahogany" in beds almacigueras and of chime in a temporary fish-pond in the El Porvenir Experimental Station and to evaluate the biomass in three periods of three consecutive months. b) To determine the quantity of captured carbon, from the biomass of the species of "Marupa", "Bolaina", "Capirona" and "Mahogany"; evaluated in three periods of three consecutive months. e) To realize the statistical tests and the analysis of the quantitative evaluations in the studied species. The factors of study were constituted by three evaluations of three consecutive months which consísted of sacríficíng 3 plants for bony specíes 12 plants in total for every evaluation doing a total of36 plants sacrificed in all the time ofthe study. The experimental used design was that of experimental blocks at random, with 4 repetitions. The compilation of information was realized for the determination of bíomass in the forest plantations of "Marupa", "Bolaina", "Capirona" and "Mahogany". All these samples were taken to the specialized laboratory of the National Instítute of Agrarian Innovation- "El Porvenir "-Tarapoto. Which hadas purpose verify the efficiency ofthe field results that was achieved to study: l. The biomass is the total sum of the organic matter that one finds in an ecosystem of a certain moment and expresses in terms of dry weight, the biomass found in the species "Marupa" in the I, the II and III Evaluation was of 0.18, 0.15 and 0.23 kg respectively; in the species "Capirona" was 0.14, O.ll and 0.19 kg respectively for each assessment; in the species "Bolaina" was 0.14, 0.10 and 0.33 kg respectively, and finally in the species "Mahogany" was 0.10, 0.08 and 0.11 kg for each assessment. It was noted that the humidity percentage is higher in the "II" assessment, with a percentage of 55.30 % between the 4 species. 2. The total number of carbon sequestration and C02 in the forest plantations by species "Marapa", "Capirona", "Bolaina" and "Mahogany", in the Agricultural Experiment Station " El Porvenir " by year is: O, 199 Kg/C/site/year and 0.7277 kg/C02/site/year in the species "Marapa"; O, 142 kg/C/site/year and 0.5203 kg/C02/site/year in the species "Capirona"; 0,219 kg/C/site/year and O. 8020 kg/C02/site/year in the species "Bolaina"; 0,121 kg/C/site/year and 0.4430 kg/C02/site/year in the species " Caoba " 3. It was found that during the development of the present investigation, the greater amount of carbon and C02 captured, and it was in the kind of "Bolaina" with 0,219 kg/C/site/year and 0.8020 kg/C02/site/year. 4. It existed significance between the treatments (species) and blocks.